2009
DOI: 10.1016/s1734-1140(09)70081-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and pharmacology of melatonin in relation to biological rhythms

Abstract: Melatonin is an evolutionarily conserved molecule that serves a time-keeping function in various species. In vertebrates, melatonin is produced predominantly by the pineal gland with a marked circadian rhythm that is governed by the central circadian pacemaker (biological clock) in the suprachiasmatic nuclei of the hypothalamus. High levels of melatonin are normally found at night, and low levels are seen during daylight hours. As a consequence, melatonin has been called the "darkness hormone". This review sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
202
0
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(221 citation statements)
references
References 326 publications
1
202
0
18
Order By: Relevance
“…At present only two of the numerous synthesized ligands of melatonin receptors are of therapeutic importance: agomelatine (Valdoxan®) -for the treatment of depression and ramelteon (Rozerem®) -for the treatment of primary insomnia characterized by difficulty with sleep onset. Recent phase II and phase III studies have demonstrated that tasimelteon (VEC-162; a high affinity agonist of human MT1 and MT2 receptors) may have therapeutic potential for transient insomnia in circadian rhythm sleep disorders [37] .…”
Section: Introductionmentioning
confidence: 99%
“…At present only two of the numerous synthesized ligands of melatonin receptors are of therapeutic importance: agomelatine (Valdoxan®) -for the treatment of depression and ramelteon (Rozerem®) -for the treatment of primary insomnia characterized by difficulty with sleep onset. Recent phase II and phase III studies have demonstrated that tasimelteon (VEC-162; a high affinity agonist of human MT1 and MT2 receptors) may have therapeutic potential for transient insomnia in circadian rhythm sleep disorders [37] .…”
Section: Introductionmentioning
confidence: 99%
“…30 Melatonin is also known as the darkness hormone and is produced by the pineal gland that responds to darkness by causing sleepiness consequently high levels of melatonin are found at night vs. low levels during daytime. 31 During shorter days of winter, as days become darker, melatonin production increases and makes people sleepy and lethargic, affecting their circadian bio-physiological rhythms with altered sleep/wake cycle, thus causing some people to become depressed. 24 Circadian rhythms also known as the body's internal biological 24-hour clock are entrained to respond to rhythmic dark-light changes that occur at certain times during the day and in each season.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…1.). All of the components necessary for the production of melatonin are active within the pineal gland, which is the main site of production (Axelrod 1974;Zawilska, Skene et al 2009). The first step is the conversion of the dietary amino acid tryptophan to 5-hydroxytryptophan by the enzyme tryptophan hydroxylase (TPH); the second step involves the conversion of 5-hydroxytryptophan to serotonin via the enzyme aromatic L -amino acid decarboxylase (AADC); serotonin is converted in the third step to N-acetylserotonin by the enzyme arylalkylamine-Nacetyltransferase (AANAT); the final step is the O-methylation of N-acetylserotonin to melatonin by the enzyme hydroxyindole-O-methyltransferase (HIOMT).…”
Section: Melatonin Precursorsmentioning
confidence: 99%
“…In the majority of species studied to date, whether they are diurnally or nocturnally active, there is a circadian secretion pattern of melatonin with high levels present at night and low levels during the day (Zawilska, Skene et al 2009). The onset of darkness following a period of light leads to an increase in pineal AANAT and melatonin levels in phase with each other (Wilkinson, Arendt et al 1977).…”
Section: Circadian Melatonin Rhythmsmentioning
confidence: 99%